Is Behavioral Economics Doomed? : The Ordinary versus the Extraordinary - K. Levine, David (Open Book Publishers, 2012)
It is fashionable to criticize economic theory for focusing too much on rationality and ignoring the imperfect and emotional way in which real economic decisions are reached. All of us facing the global economic crisis wonder just how rational economic men and women can be. Behavioral economics$1 (Ban effort to incorporate psychological ideas into economics$1 (Bhas become all the rage. This book by well-known economist David K. Levine questions the idea that behavioral economics is the answer to economic problems. It explores the successes and failures of contemporary economics both inside and outside the laboratory. It then asks whether popular behavioral theories of psychological biases are solutions to the failures. It not only provides an overview of popular behavioral theories and their history, but also gives the reader the tools for scrutinizing them. Levine$1 (Bs book is essential reading for students and teachers of economic theory and anyone interested in the psychology of economics.s
English
Keywords: game theory; economics; psychology; microeconomics; rationality; economic models; economic theory; Behavioral economics; Nash equilibrium; Risk aversion; Subgame perfect equilibrium